Strategi Pengembangan Kampung Silat, Rawa Belong Sebagai Destinasi Wisata - Regina Dewi Hanifa; Regita Pratikawati (Politeknik Sahid, 2020)
The role of tourist destinations is essential, especially in packaging people’s life and culture into a tourist attraction. Astuti (2017) states that cultural tourism has a 60% role in supporting the world of tourism in Indonesia itself. One of the areas that will be developed by the Provincial Government of DKI Jakarta Barat as a Cultural Tourism Destination, especially with silat attractions as a characteristic is Silat Village, which is located in the Rawa Belong area, which is known as a shopping center for fresh flowers by the surrounding community. In drawing up a destination, a strategy is needed based on the potential of an area. In line with the objectives of the government, the purpose of this study is to review the potential of the Rawa Belong area as a cultural tourism destination and to find out what efforts these tourist destinations have made. This research methodology uses a qualitative approach with descriptive methods. By using components tourism destinations which consist of 5A, namely Attraction, Accessibility, Amenity, Activity, and Ancillary Service (additional facilities) as study material and explore the potential of the area, the authors use primary data which taken directly during observation and interviews and secondary data based on literature related to the area. The informants used are key informants, regular informants and additional informants. Using a SWOT analysis, a matrix is presented to determine which strategy is appropriate for the development of Kampung Silat Rawa Belong. The results of this study indicate that many potentials that are possessed a strength for Kampung Silat Rawa Belong are the main keys in the strategy of the place. The good thing is that this area can focus on one of the principal attractions, namely the Silat Arts. So that later all other attractions owned by the area can become supporting attractions and become one unit in shaping sustainable tourism going forward. So that the direction of the tourist destination of Kampung Silat itself can be formed, and is willing to become a tourist destination that can be visited by tourists. In addition, the role of the government is also quite much needed in pioneering the area apart from infrastructure, the economy, as well as how the role of the organization as an extension of the government can run a tourism unit that is there.